2020
DOI: 10.1155/2020/7298687
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Exosomes Derived from Different Cell Sources and Cardiovascular Diseases

Abstract: Exosomes can reach distant tissues through blood circulation to communicate directly with target cells and rapidly regulate intracellular signals. Exosomes play an important role in cardiovascular pathophysiology. Different exosomes derived from different sources, and their cargos have different mechanisms of action. In addition to being biomarkers, exosomes also have a certain significance in the diagnosis, treatment, and even prevention of cardiovascular diseases. Here, we provide a review of the up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 98 publications
0
8
0
1
Order By: Relevance
“…HSPs are enriched in cardiac exosomes and they show a key role in cellular survival and protection to multiple stressful events. HSP20 is an important member of the HSP family and is present in cardiomyocyte-derived circulating exosomes, promoting the formation of myocardial neovascularization and blocking tissue necrosis factor α (TNF-α) and interleukin 1β (IL-1β) to reduce the risk of MI [ 151 ]. HSP20 is released in physiological conditions, but its secretion is increased in MI and under stress conditions such as ischemia/reperfusion [ 152 ].…”
Section: Exosomes In Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPs are enriched in cardiac exosomes and they show a key role in cellular survival and protection to multiple stressful events. HSP20 is an important member of the HSP family and is present in cardiomyocyte-derived circulating exosomes, promoting the formation of myocardial neovascularization and blocking tissue necrosis factor α (TNF-α) and interleukin 1β (IL-1β) to reduce the risk of MI [ 151 ]. HSP20 is released in physiological conditions, but its secretion is increased in MI and under stress conditions such as ischemia/reperfusion [ 152 ].…”
Section: Exosomes In Cardiovascular Diseasesmentioning
confidence: 99%
“…It is also well known that, the exosomal proteins derived from MSCs promote angiogenesis, decrease cardiomyocyte apoptosis and ventricular remodelling, and protect the cardiac function [ 151 ]. Ma et al collected MSCs from human umbilical cords and evaluated whether exosomes released from Akt-overexpressing MSCs had a cardioprotection role and stimulated angiogenesis in AMI rat model [ 167 ].…”
Section: Exosomes In Cardiovascular Diseasesmentioning
confidence: 99%
“…Our current study delves into the role of AT- and plasma-derived adipomes in the pathogenesis of cardiomyopathy. The myocardium can be regulated by exosomes derived from various cell types, 110 , 111 including exosomes produced by T. cruzi . 112 Studies have demonstrated that T. cruzi -derived EVs exert immunomodulatory effects with potential applications in CD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As a kind of extracellular vesicles, exosomes can be released from a variety of cells including fibroblasts, intestinal ECs, neurons, and adipocytes [59,60] . Exosomes tend to move through the intercellular junctions, leave their initial fluid and move to adjacent areas of tissues, and communicate with neighboring cells through cell-cell connections, which is the primary function of exosomes.…”
Section: Uptake Of Exosomesmentioning
confidence: 99%